2021
DOI: 10.1088/1755-1315/674/1/012096
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of lead (Pb) on hatching rate and larvae abnormalities of Nile Tilapia (Oreochromis niloticus)

Abstract: Like other fish, Nile tilapia (Oreochromis niloticus) is one species that potentially exposed to pollutants, including lead (Pb). However, the impact of Pb exposure on hatching rate and larvae development of Nile tilapia is still not investigated. Therefore, this study aimed to examine the toxic effect of Pb exposure on hacthing rate and larvae abnormalities of Nile tilapia. A total of 2,400 fertilized eggs of Nile tilapia was distributed to control and 3 treatment group namely: treatment A (0.21 mg/L PbCl2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In line with the results found in this study, Ayegbusi [27] observed a decrease in SGR of catfish with increasing concentrations of lead (Pb) in the growth medium, while Opute [28] an the other scholars also reported a decrease in SGR and a significant increase in juvenile catfish mortality when exposed to the herbicide atrazine. It was also observed that toxic waste could also affect larvae growth, as reported that toxic waste with Pb content could significantly decreased the hatching rate and induced the abnormalities of Tilapia larvae [29]. It was also observed a decrease in growth performance and a significant increase in mortality in catfish exposed to domestic waste [26].…”
Section: Catfish Growthmentioning
confidence: 82%
“…In line with the results found in this study, Ayegbusi [27] observed a decrease in SGR of catfish with increasing concentrations of lead (Pb) in the growth medium, while Opute [28] an the other scholars also reported a decrease in SGR and a significant increase in juvenile catfish mortality when exposed to the herbicide atrazine. It was also observed that toxic waste could also affect larvae growth, as reported that toxic waste with Pb content could significantly decreased the hatching rate and induced the abnormalities of Tilapia larvae [29]. It was also observed a decrease in growth performance and a significant increase in mortality in catfish exposed to domestic waste [26].…”
Section: Catfish Growthmentioning
confidence: 82%
“…Similar impeding effects was also found in Anguilla anguilla exposed to mercury (Nowosad et al, 2021) (Table 1). Deformities in Nile tilapia larvae including lordosis, kyphosis, and curved tail in Oreochromis niloticus was noted on exposure to 0.21 ppm, 0.42 ppm, 0.63 ppm lead for 10 days (Melanie et al, 2021) (Table 1).…”
Section: O N L I N E C O P Ymentioning
confidence: 99%